PARENT-CHILD RELATIONSHIPS AFTER PARENTAL SEPARATION: - Moon, Michelle H (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Research with adult children of divorce (ACD) has contributed to literature suggesting the adverse long-term effects of parental separation and divorce. The role of the parent-child relationship following parental separation, when a parents availability and support might well be especially important for a child, particularly if there is ongoing parental conflict, has received little empirical attention and was examined here.The present investigation was designed to assess ACDs retrospective ratings of their mothersand fathers parenting in the two years following parental separation. ACDs reports of each of their parents dating behaviors as well as the conflict they remembered between their parents during this period were also examined.The results of the present investigation indicate that ACD view their mothers and fathers parenting behavior in the two years following separation as an important factor related to their current relationships with each of their parents.